Postpartum Depression: The Forgotten Mother Experience - Yunike; Ira Kusumawaty; Yuyun Yuliyani; Rini Sugiarti; Fendy Suhariadi (Jurnal Penelitian Pendidikan IPA, 2023)
Background: Postpartum blues refers to the temporary mood depression experienced by new mothers due to hormonal changes, having new responsibilities due to having a baby, and parenting duties. This condition is a mood disorder that occurs after childbirth, reflecting psychological dysregulation. Purpose: This literature study aims to identify factors that influence the occurrence of postpartum blues, signs and symptoms, and the prevention and management of postpartum blues. Method: The method used in this literature study is a literature search from various sources, such as academic journals and online articles. A literature search was performed using keywords related to postpartum blues. Results: There are six studies on postpartum blues; factors that influence postpartum blues are primigravida mothers, age, salary, education, employment, breastfeeding process, health education after delivery, type of delivery, induction of labour and complications of labour, parity, pregnancy status, mother's readiness, readiness for childbirth, marital satisfaction, husband's support, and social support, as well as having economic tensions. While the signs and symptoms are sadness, crying easily, easily defeated, easily anxious, sensitive, unstable, feeling unable to care for the baby, feeling guilty, disturbed sleep, and eating disorders. Management and prevention of postpartum blues include massage, physical activity, use of vitamins and hormones, acupressure, and massage therapy. Conclusion: Health workers need to carry out screening and early detection so that appropriate treatment can be given and does not lead to postpartum depression.